Enhanced Circularly Polarized Luminescence Activity in Chiral Platinum(II) Complexes With Bis- or Triphenylphosphine Ligands - Yang, Qian-Ying; Zhang, Hua-Hong; Han, Xue-Ling; Weng, Shi-Dao; Chen, Yuan; Wu, Jia-Li; Han, Li-Zhi; Zhang, Xiao-Peng; Shi, Zai-Feng (Frontiers in Chemistry, 2020)
Distinct circularly polarized luminescence (CPL) activity was observed in chiral (C∧N∧N)Pt(II) [(C∧N∧N) = 4,5-pinene-6′-phenyl-2,2′-bipyridine] complexes with bis- or triphenylphosphine ligands. Compared to the pseudo-square-planar geometry of chiral (C∧N∧N)Pt(II) complexes with chloride, phenylacetylene (PPV) and 2,6-dimethylphenyl isocyanide (Dmpi) ligands, the coordination configuration around the Pt(II) nucleus of chiral (C∧N∧N)Pt(II) complexes with bulk phosphine ligands is far more distorted. The geometry is straightforwardly confirmed by X-ray crystallography. The phosphines' participation enhanced the CPL signal of Pt(II) complexes profoundly, with the dissymmetry factor (glum) up to 10−3. The distorted structures and enhanced chiroptical signals were further confirmed by time-dependent density functional theory (TD-DFT) calculations.